2013
DOI: 10.1680/geot.sip13.p.011
|View full text |Cite
|
Sign up to set email alerts
|

Double-structure effects on the chemo-hydro-mechanical behaviour of a compacted active clay

Abstract: This work presents an insight into double-structure effects on the coupled chemo-hydro-mechanical behaviour of a compacted active clay. In the first part, selected pore size distribution curves are introduced, to highlight the influence of solute concentration on the evolution of the microstructure of compacted samples. An aggregated structure with dual-pore network is induced by compaction even at relatively high water contents. This structural arrangement is enhanced by salinisation, and has a notable influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(48 citation statements)
references
References 44 publications
2
46
0
Order By: Relevance
“…Many authors discussed the possibility that pore water pressure may change during the process of exposure to a fluid different from the pore fluid, as an effect of osmotic processes at the specimen scale (Mitchell et al, 1973;Barbour and Fredlund, 1989;Gajo and Loret, 2004;Musso et al, 2013), as well as an effect of the diffusion of high concentration ionic front (Santamarina and Fam, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Many authors discussed the possibility that pore water pressure may change during the process of exposure to a fluid different from the pore fluid, as an effect of osmotic processes at the specimen scale (Mitchell et al, 1973;Barbour and Fredlund, 1989;Gajo and Loret, 2004;Musso et al, 2013), as well as an effect of the diffusion of high concentration ionic front (Santamarina and Fam, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The pore size density (PSD) functions, for both saturated and unsaturated soils, obtained from mercury intrusion porosimetry (MIP) have been shown to evolve as a result of hydraulic, mechanical and chemical changes (Delage and Lefebvre, 1984;Delage et al, 1996;Romero et al, 1999;Simms and Yanful, 2001;Koliji et al, 2006;Casini et al, 2012;Musso et al, 2013;Wang et al, 2013). Despite this, there is still limited understanding of how the soil microstructure evolves during combined hydraulic and mechanical paths.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, any microstructural changes can be attributed to the salt crystallization rather than to any osmotic effects as sometimes observed on compacted soils [3,11]. It can be observed that the maximum mercury intrusion void ratio (e MIP ) of the specimens tends to decrease with increasing concentrations (Fig.…”
Section: Resultsmentioning
confidence: 80%
“…Moisture and soluble salts it contains migrate upwards under suction gradients due to evaporation and, close to the road pavement surface, the salts tend to accumulate in a crystalline form, which can result in significant damage to thin bituminous surfacings [12][13][14] because of the increase in volume associated with salt precipitation. Although some studies examined the microstructural changes in compacted soils subjected to salinization [3,11], very few of them looked at the microstructural effects associated with naturally occurring salt crystallization on granular road pavement materials. In particular, little effort was made to quantify the microstructural changes in terms of pore size distribution (inferred from mercury intrusion porosimetry), despite the fact that understanding microscale phenomena often helps explaining macroscopic behaviors [6,16].…”
Section: Introductionmentioning
confidence: 99%